Budgetary Influence under Information Asymmetries: Evidence from Nigeria's Sub-National Agricultural Investments - Mogues, Tewodaj (2019)
Tewodaj Mogues POLICY SEMINAR Information, Governance, and Rural Service Delivery Co-Organized by IFPRI and the CGIAR Research Program on Policies, Institutions, and Markets (PIM)